A method for the extraction and partial isolation of the glycosides from the leaves of Cananga odorata - Polintan, Paulino
50 grams of the air-dried leaves of Cananga odorata were macerated with 90% alcohol as solvent. This macerate was concentrated to a syrupy consistency by distillation under reduced pressure then evaporated spontaneously to obtain a greenish mass. This mass is extracted with successive portions of acetone to remove the green color. This brown residue left is then isolated from the insoluble solids and impurities by column chromatography. The methanol eluates are combined and evaporated to dryness on a water bath to yield slightly greenish solids of the glycosides.